Seleção de áreas de prospeção mineira com recurso aos SIG na região de Lagoa Negra (NW de Portugal) - Cláudio Paulo (2014)
The hydrothermal mineralization veins are abundant in northern Portugal, their exploration and exploitation dates back at least to the time of the Roman occupation, which raises the interest of mining companies in the acquisition of exploration areas. The study area is within an exploration area of "Klondike Gold Portugal" mining company, acquired recently by " Medgold Resources ". The concession license is known as Balazar and located at NW of Valongo Belt. The study was centered on " Lagoa Negra " zone where is known the Sb-Au mineralization. All the information about the existing geological mapping, stream sediments and mineralometry campaigns were introduced into a Geographic Information System (GIS) which with both components "Data and Knowledge Driven", created a predictive map that identifies the locations to perform detailed exploration.